Electric double layer capacitors for ac filtering made from vertically oriented graphene nanosheets on aluminum. (January 2017) - Premathilake, Dilshan; Outlaw, Ronald A.; Parler, Samuel G.; Butler, Sue M.; Miller, John R.
Abstract: Vertically oriented graphene nanosheets have been grown on aluminum foil for the first time and used to make electrical double layer capacitors. The singular difficulty of aluminum to be a viable substrate is the stability of the native surface oxide, Al2 O3, that inhibits good ohmic contact. The nanosheets were grown by radio frequency plasma enhanced chemical vapor deposition from C2 H2 feedstock at a plasma power of 1100 W. The growth method first thins the Al surface oxide by RF plasma sputtering and then rapidly covers the surface with carbon to prevent further oxidation before nanosheet growth, thus allowing ohmic connection between the graphene and the aluminum. The graphene films, grown at a substrate temperature of 620 °C show good verticality and openness. The Raman D peak to G peak ratio varied from 0.85 to 2.0 as a function of flow rate. The specific capacitance at 120 Hz was approximately 80 μF/cm 2 (1.3 μm sheet height), which is greater than that achieved from vertically oriented graphene nanosheets grown on nickel foil for similar nanosheet height. The phase angle of capacitors fabricated with these electrodes was near −90° at 120 Hz, making EDLCs suitable for ac filter applications presently dominated by aluminum electrolytic capacitors.